\(a^2+b^2=1\)Và \(a^4+b^4=\frac{1}{2}\) Tinh \(a^{2018}+b^{2018}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{a^4}{2018}+\frac{b^4}{2019}=\frac{1}{4037}\)
\(\Leftrightarrow\frac{2019a^4+2018b^4}{2018\cdot2019}=\frac{a^2+b^2}{2018+2019}\)
\(\Leftrightarrow\left(2018+2019\right)\left(2019a^4+2018b^4\right)=2018\cdot2019\left(a^2+b^2\right)\)
\(\Leftrightarrow2019^2\cdot a^4+2018^2\cdot b^4+2018\cdot2019\cdot a^4+2018\cdot2019b^4=2018\cdot2019\cdot a^2+2018\cdot2019\cdot b^2\)
\(\Leftrightarrow2019^2\cdot a^4+2018^2\cdot b^4=2018\cdot2019\cdot a^2\left(1-a^2\right)+2018\cdot2019\cdot b^2\left(1-b^2\right)\)
\(\Leftrightarrow\left(2019a^2\right)^2+\left(2018b^2\right)^2=2\cdot2018\cdot2019\cdot a^2\cdot b^2\)
\(\Leftrightarrow\left(2019a^2-2018b^2\right)=0\)
\(\Leftrightarrow2019a^2=2018b^2\Leftrightarrow\frac{a^2}{2018}=\frac{b^2}{2019}=\frac{a^2+b^2}{2018+2019}=\frac{1}{4037}\)
\(\Rightarrow\frac{a^{2018}}{2018^{10009}}=\frac{b^{2018}}{2019^{1009}}=\frac{1}{4037^{1009}}\)
\(\Rightarrow P=\frac{2}{4037^{1009}}\)
a, \(M=\frac{3}{2}\cdot\frac{4}{3}\cdot\cdot\cdot\cdot\frac{2018}{2017}\cdot\frac{2019}{2018}=\frac{3.4...2019}{2.3...2018}=\frac{2019}{2}\)
b, c cùng 1 câu phải k
ta có: \(A=1-\frac{1}{2}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{2017}-\frac{1}{2018}\)
\(=\left(1+\frac{1}{3}+...+\frac{1}{2017}\right)-\left(\frac{1}{2}+\frac{1}{4}+...+\frac{1}{2018}\right)\)
\(=\left(1+\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2018}\right)-2\left(\frac{1}{2}+\frac{1}{4}+...+\frac{1}{2018}\right)\)
\(=1+\frac{1}{2}+...+\frac{1}{2018}-\left(1+\frac{1}{2}+...+\frac{1}{1009}\right)\)
\(=\frac{1}{1010}+\frac{1}{1011}+...+\frac{1}{2018}=B\)
\(\Rightarrow\frac{A}{B}=1\Rightarrow\left(\frac{A}{B}\right)^{2018}=1^{2018}=1\)
A,\(M=\frac{3}{2}\cdot\frac{4}{3}....\frac{2018}{2017}\cdot\frac{2019}{2018}=\frac{4\cdot3...2019}{2\cdot3...2018}=\frac{2019}{2}\)
NHA
HỌC TỐT
\(\frac{1}{1.3}+\frac{1}{3.5}+...+\frac{1}{x.\left(x+2\right)}=\frac{20}{41}\)
\(\Leftrightarrow\frac{1}{2}.\left(1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+...+\frac{1}{x}-\frac{1}{x+2}\right)=\frac{20}{41}\)
\(\Leftrightarrow\frac{1}{2}.\left(1-\frac{1}{x+2}\right)=\frac{20}{41}\)
\(\Leftrightarrow1-\frac{1}{x+2}=\frac{20}{41}\div\frac{1}{2}\)
\(\Leftrightarrow1-\frac{1}{x+2}=\frac{40}{41}\)
\(\Leftrightarrow\frac{1}{x+2}=1-\frac{40}{41}\)
\(\Leftrightarrow\frac{1}{x+2}=\frac{1}{41}\)
\(\Leftrightarrow x+2=41\)
\(\Leftrightarrow x=41-2\)
\(\Leftrightarrow x=39\)